If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -6 = 10x + -13 Reorder the terms: -6 + 17x = 10x + -13 Reorder the terms: -6 + 17x = -13 + 10x Solving -6 + 17x = -13 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -6 + 17x + -10x = -13 + 10x + -10x Combine like terms: 17x + -10x = 7x -6 + 7x = -13 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 + 7x = -13 + 0 -6 + 7x = -13 Add '6' to each side of the equation. -6 + 6 + 7x = -13 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = -13 + 6 7x = -13 + 6 Combine like terms: -13 + 6 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 | | 3+3=8x+23 | | (x)(x)-11x+18=0 | | 3/2y-8=-5 | | 7x+20=3x+36 | | 2x+9=2x+3 | | x^2=5y+35 | | 4+3x=6x-83x-12 | | -3x+5(-6x+4)-(-30x+16)=-9(x-5) | | 9k^2+29k+8=0 | | 16x-22x=1/2 | | 6p+11=3p-4 | | 6z-5=3z-4 | | 16x/-22x=1/2 | | X-80=100 | | 6/7y=-18/77 | | 5/7x-3=2 | | -0.1x+4=11 | | 2x-(5x+9)=6(2x+1) |